Towards a greener Visegrád group: Progress and challenges in the context of the European Green Deal - Tobias Riepl; Zuzana Zavarská (The Vienna Institute for International Economic Studies (wiiw), 2023)
The European Green Deal, which aims to steer the EU towards climate neutrality, has traditionally been met with a degree of reluctance by the Visegrád countries. The convergence to green targets represents a particular challenge for these economies, given their fossil fuel-intensive industrial orientation and the high labour market exposure of certain regions to coal mining. In reality, progress with the green transition in the region has been mixed. The expansion of renewables has been scaled up in Slovakia and partially in Poland, but has been stagnating in Czechia and even decreasing in Hungary. In the building sector, states' retrofitting schemes are working well in terms of bringing down energy consumption in housing, despite the limited adoption of innovative heating techniques. In transport, the region focuses almost excessively on highly contested biofuels, whereas the use of green electricity for road transportation and rail systems remains negligible. Still, the Visegrád group has accomplished a remarkable catch-up in enhancing its energy efficiency in recent years, albeit still belonging to the most CO2-intensive regions in Europe. There are numerous obstacles to the green transition in the region, including lower starting points creating path-dependencies, lesser (albeit growing) social recognition of the climate crisis, and the fear of social fallout due to high employment in the coal and automobile sectors. At the same time, the Russian aggression against Ukraine has revealed the vulnerabilities of fossil fuel dependency, and as a result has broadened the pro-green-transition coalition. While it remains to be seen whether this momentum will turn into action, green pioneers such as Austria can take on a more active role by cooperating with and supporting the Visegrád countries in reaching their climate targets. This includes deepening cooperation on green electricity projects, strengthening basic research through cross-country consortia, or incentivising investment in the building and transportation sector, in which Austrian firms are well-positioned.
Keywords: O13; Q58; Q42; 330; Visegrád countries; European Green Deal; green transition; renewable energy